Comparison between the FUZZY-ARFIMA model and the Hybrid ARFIMA -FUZZY model with application to agricultural data in the city of Mosul - Ahmed, Rehab Talal; Ibrahim, Omar salim (Statistics, Optimization & Information Computing, 2024)
In this research, we studied forecasting based on time series data for red onion prices in Nineveh Governorate using model ARFIMA Autoregressive fractionally integrated moving average. A ARFIMA-FUZZY (FTS) hybrid model was proposed This model has the advantage and strength of the ARFIMA partial autoregressive integral in addition to the FUZZY-ARFIMA model and compared them with each other using evaluation criteria (BIC). For prediction, which is calculated using the statistical program R. The results showed that the ARFIMA-FUZZY (FTS) hybrid model is the best because it has the lowest (BIC) values. It is also the highest in forecast efficiency because it has the lowest values of forecast accuracy metrics (MSE, RMSE, MAE) and was chosen as the best forecast model.